One small edit for humans, one giant edit for humankind? Points and questions to consider for a responsible way forward for gene editing in humans. (January 2018) - Howard, Heidi; El, Carla; Forzano, Francesca; Radojkovic, Dragica; Rial-Sebbag, Emmanuelle; Wert, Guido; Borry, Pascal; Cornel, Martina
Abstract Gene editing, which allows for specific location(s) in the genome to be targeted and altered by deleting, adding or substituting nucleotides, is currently the subject of important academic and policy discussions. With the advent of efficient tools, such as CRISPR-Cas9, the plausibility of using gene editing safely in humans for either somatic or germ line gene editing is being considered seriously. Beyond safety issues, somatic gene editing in humans does raise ethical, legal and social issues (ELSI), however, it is suggested to be less challenging to existing ethical and legal frameworks; indeed somatic gene editing is already applied in (pre-) clinical trials. In contrast, the notion of altering the germ line or embryo such that alterations could be heritable in humans raises a large number of ELSI; it is currently debated whether it should even be allowed in the context of basic research. Even greater ELSI debates address the potential use of germ line or embryo gene editing for clinical purposes, which, at the moment is not being conducted and is prohibited in several jurisdictions. In the context of these ongoing debates surrounding gene editing, we present herein guidance to further discussion and investigation by highlighting three crucial areas that merit the most attention, time and resources at this stage in the responsible development and use of gene editing technologies: (1) conducting careful scientific research and disseminating results to build a solid evidence base; (2) conducting ethical, legal and social issues research; and (3) conducting meaningful stakeholder engagement, education and dialogue.